2021
DOI: 10.1093/plphys/kiab009
|View full text |Cite
|
Sign up to set email alerts
|

A mixed-linkage (1,3;1,4)-β-D-glucan specific hydrolase mediates dark-triggered degradation of this plant cell wall polysaccharide

Abstract: The presence of mixed-linkage (1,3;1,4)-β-D-glucan (MLG) in plant cell walls is a key feature of grass species such as cereals, the main source of calorie intake for humans and cattle. Accumulation of this polysaccharide involves the coordinated regulation of biosynthetic and metabolic machineries. While several components of the MLG biosynthesis machinery have been identified in diverse plant species, degradation of MLG is poorly understood. In this study, we performed a large-scale forward genetic screen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 71 publications
5
24
0
Order By: Relevance
“…Barley isoenzyme EI was induced in dark-incubated barley seedlings and MLG content decreased significantly (Roulin et al, 2002). A similar result was found in maize that the expression of MLGH1, a gene encoding lichenase, was increased during the night (Kraemer et al, 2021). To determine whether genes encoding lichenases in B. distachyon are induced by darkness and to examine further the response of lch1 mutants to darkness, 3-week-old wildtype and lch1 plants were incubated under a 16-h light/8-h dark cycle (0 h), or in complete darkness for 24, 48, and 72 h (Figure S8).…”
Section: Transcription Of Bdlch1 Is Induced In Leaves Of Darkincubate...supporting
confidence: 76%
See 1 more Smart Citation
“…Barley isoenzyme EI was induced in dark-incubated barley seedlings and MLG content decreased significantly (Roulin et al, 2002). A similar result was found in maize that the expression of MLGH1, a gene encoding lichenase, was increased during the night (Kraemer et al, 2021). To determine whether genes encoding lichenases in B. distachyon are induced by darkness and to examine further the response of lch1 mutants to darkness, 3-week-old wildtype and lch1 plants were incubated under a 16-h light/8-h dark cycle (0 h), or in complete darkness for 24, 48, and 72 h (Figure S8).…”
Section: Transcription Of Bdlch1 Is Induced In Leaves Of Darkincubate...supporting
confidence: 76%
“…MLG content in leaves of dark-incubated plants decreased, which is consistent with the induction of EI by darkness. Recently, Kraemer et al (2021) identified a lichenase in maize named MLGH1, and this enzyme is involved in MLG degradation during the night. The mutant mlgh1 contained more MLG and showed no significant growth defects.…”
Section: Introductionmentioning
confidence: 99%
“…Barley HvEI-HvEII enzymes are 1,3;1,4-β- D -glucan endohydrolases ( Varghese et al, 1994 ). The Zm00001d038049 gene matches the maize GRMZM2G137535 gene, which was demonstrated to be an MLG-degrading enzyme in maize leaves ( Kraemer et al, 2021 ). The protein content of Zm00001d038049 in roots was negligible ( Supplementary Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…At present, GHs are thought to participate in cell wall polysaccharide turnover; although neither cause nor effect of this intensive metabolism is understood yet ( Barnes and Anderson, 2018 ). For instance, MLG turnover is coupled to the day and night cycle in maize leaves via the expression of an MLG-specific hydrolase ( Kraemer et al, 2021 ). GHs take part in cellulose microfibril formation ( Nicol et al, 1998 ; Lane et al, 2001 ; Szyjanowicz et al, 2004 ) and control the angle of cellulose microfibrils ( Derba-Maceluch et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Intragenic complementation has not been observed among alleles with mutations in different CSLD1 domains of Lotus japonicas [96], suggesting that the CSLD1 has not yet undergone the complete functional differentiation. CslF6 and CslH have a functional role in the synthesis of mixed-linkage (1,3;1,4)-β-glucan (MLG [97]), and the sequence divergence of the Csl genes we found is likely a reflection of their functional divergence although MLG synthesis is tightly regulated and thus maximizing the yield of end-product cellulose might be difficult. For example, isoforms may utilize the same donor but a different acceptor molecule in the synthesis of the same polysaccharide, and thus, having multiple genes may be a requirement for synthesis of some types of plant polysaccharides [58].…”
Section: Discussionmentioning
confidence: 99%